Integrating Tourism Marketing into ESP: Teachers’ Perspectives from a Vocational Education Context - Bidari Andaru Widhi; Baiq Nadia Nirwana; Zamroni (International Journal of Research in Education, 2026)
This study examines teachers’ perceptions of integrating tourism marketing concepts into English for Specific Purposes (ESP) instruction at SMKN 1 Gerung, a vocational high school that offers a Tourism Destination major. As the tourism industry increasingly demands graduates with strong English proficiency and marketing communication skills, ESP programs are expected to provide learning experiences that reflect real professional practices. Teachers’ perceptions are crucial in this process because their beliefs, pedagogical knowledge, and instructional decisions directly influence the implementation and success of curriculum integration. Adopting a qualitative descriptive design, data were collected from 8 ESP teachers through semi-structured interviews, supported by document analysis and classroom observations to ensure methodological triangulation. Qualitative analysis revealed that teachers generally hold positive views toward integrating tourism marketing, as they believe it can improve students’ language proficiency, increase their motivation, and strengthen their ability to communicate effectively in workplace-related contexts. However, several challenges were identified, including limited availability of authentic and up-to-date teaching materials, insufficient professional development in tourism marketing, and weak collaboration between the school and tourism industry stakeholders. These challenges hinder teachers’ ability to design industry-relevant ESP lessons. The study highlights the need for curriculum updates, the development of authentic tourism marketing resources, and structured professional development programs. Overall, the findings offer important insights into improving curriculum design, teacher professional development and school-industry collaboration to enhance the quality, relevance, and industry alignment of ESP instruction in tourism-focused vocational education settings.